2021
DOI: 10.1111/adb.13009
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced escalation of alcohol self‐administration, anxiety‐like behavior, and elevated amygdala Avp expression in a susceptible subpopulation of rats

Abstract: Comorbidity between alcohol use and anxiety disorders is associated with more severe symptoms and poorer treatment outcomes than either of the conditions alone. There is a well‐known link between stress and the development of these disorders, with post‐traumatic stress disorder as a prototypic example. Post‐traumatic stress disorder can arise as a consequence of experiencing traumatic events firsthand and also after witnessing them. Here, we used a model of social defeat and witness stress in rats, to study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This mouse finding is in accordance with other recent rodent data, showing that pronounced effects of ethanol characterise animals expressing maladaptive behavioural responses to stress. These effects were observed either with the CPP paradigm (Bahi & Dreyer, 2014; Bahi & Dreyer, 2020; Macedo et al, 2018; Yu et al, 2016), with the two‐bottle free choice paradigm (Cannady et al, 2021; Manjoch et al, 2016; Meyer et al, 2013) or with the self‐administration paradigm (Barchiesi et al, 2021; Edwards et al, 2013; Makhijani et al, 2021). Nevertheless, studies with other drugs (such as cocaine and methamphetamine) have shown that stress does not necessarily lead to potentiate the effect of the drug or increase its consumption (e.g., cocaine: Enman et al, 2015; Hadad et al, 2016; Lguensat et al, 2021; methamphetamine: Eagle & Perrine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This mouse finding is in accordance with other recent rodent data, showing that pronounced effects of ethanol characterise animals expressing maladaptive behavioural responses to stress. These effects were observed either with the CPP paradigm (Bahi & Dreyer, 2014; Bahi & Dreyer, 2020; Macedo et al, 2018; Yu et al, 2016), with the two‐bottle free choice paradigm (Cannady et al, 2021; Manjoch et al, 2016; Meyer et al, 2013) or with the self‐administration paradigm (Barchiesi et al, 2021; Edwards et al, 2013; Makhijani et al, 2021). Nevertheless, studies with other drugs (such as cocaine and methamphetamine) have shown that stress does not necessarily lead to potentiate the effect of the drug or increase its consumption (e.g., cocaine: Enman et al, 2015; Hadad et al, 2016; Lguensat et al, 2021; methamphetamine: Eagle & Perrine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite not being deeply explored, psychological stress may cause drug abuse-like behaviors similar to those who experienced stress directly. For instance, studies demonstrated increased rewarding effects of cocaine and alcohol in animals that witnessed chronic defeat stress applied to their cagemates ( Garcia-Carachure et al, 2020 ; Barchiesi et al, 2021 ). However, no studies have verified the consequences of vicarious stress in drug-induced locomotor sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to ethanol, exposure to SD increases the conditioned rewarding effects of ethanol using the CPP paradigm ( Macedo et al, 2018 ). Studies of voluntary ethanol consumption have observed increased and escalating consumption of ethanol, as well as an increased motivation to drink alcohol, in defeated animals using the oral SA paradigm ( Barchiesi et al, 2021 ; Montagud-Romero et al, 2021 ; Norman et al, 2015 ; Reguilón et al, 2020 , 2021 ; Rodríguez-Arias et al, 2016 ). Using other paradigms such as the two-bottle choice, an increase in SD-induced escalation of alcohol intake has also been observed ( Croft et al, 2005 ; Deal et al, 2018 ; Hwa et al, 2016 ; Newman et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%